2022
DOI: 10.1093/cvr/cvac116
|View full text |Cite
|
Sign up to set email alerts
|

A functional connectome signature of blood pressure in >30 000 participants from the UK biobank

Abstract: Aims Elevated blood pressure (BP) is a prevalent modifiable risk factor for cardiovascular diseases and contributes to cognitive decline in late life. Despite the fact that functional changes may precede irreversible structural damage and emerge in an ongoing manner, studies have been predominantly informed by brain structure and group-level inferences. Here, we aim to delineate neurobiological correlates of BP at an individual level using machine learning and functional connectivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…However, causal directionality has been questioned by some (21) since BPV is partly determined by the baroreflex (22), and both neurodegeneration and white matter damage due to CSVD may be associated with autonomic dysfunction (23). Numerous functional brain MRI studies have identified a central autonomic network (CAN) involved in control of blood pressure (24), heart rate (25), heart rate variability (26) and baroreflex sensitivity (27). The CAN includes grey matter regions susceptible to vascular and neurodegenerative disease in APOE4 carriers, particularly the hippocampus (10,28), amygdala (28,29) and insular cortices (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…However, causal directionality has been questioned by some (21) since BPV is partly determined by the baroreflex (22), and both neurodegeneration and white matter damage due to CSVD may be associated with autonomic dysfunction (23). Numerous functional brain MRI studies have identified a central autonomic network (CAN) involved in control of blood pressure (24), heart rate (25), heart rate variability (26) and baroreflex sensitivity (27). The CAN includes grey matter regions susceptible to vascular and neurodegenerative disease in APOE4 carriers, particularly the hippocampus (10,28), amygdala (28,29) and insular cortices (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Some people who were healthy at baseline may progress to have liver fibrosis, which may underestimate the liver-brain associations. However, given that it may take years for disease-related changes to be evident in brain structure, 47 this long time interval can allow us to observe the associations between liver fibrosis and lower GMVs. 5 Supporting evidence for the direct association of liver fibrosis with regional brain structure in the literature is sparse, but these results accord with emerging evidence relating chronic liver diseases to Alzheimer's disease (AD) pathology and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we utilized partial least squares regression (PLSR) to build the predictive model. PLSR is a widely used multivariate regression method in various fields such as bioinformatics, and neuroscience (Jiang et al, 2023; Jiang, Scheinost, et al, 2022; McIntosh et al, 1996; Meskaldji et al, 2016; Nguyen & Rocke, 2002). PLSR is particularly suitable when the number of predictors is relatively large compared to the available samples (Shen et al, 2017).…”
Section: Methodsmentioning
confidence: 99%